The Normalization of Conservative Gender Politics in Chile and the Role of Civil Society - Graf, Patricia (Frontiers in Sociology, 2020)
The article discusses two cases of gender policy making during the Chilean transition to democracy, the policy on domestic violence and the divorce law. By comparing the official discourses on these two policy projects we show that authoritarian gender regimes can resist transition to democracy despite a vivid civil society. The case of Chile was selected, on one hand, because it exhibits particularly resistant authoritarian institutional enclaves. On the other hand, Chilean women's movements are often cited as a paragon of women's movements in transitions. Despite the central role of Chilean women's movements as a strong civil society force conservative gender roles and institutions inherited from the autocratic regime (e.g., conservative divorce and reproductive rights) have remained dominant. I argue that during the time of transition conservative political actors, but also parts of civil society, negotiated on these gender roles and institutions and thereby reached a status quo. Recent cases of sexual violence in response to student’s uprisings show that this status quo is quite stable and prevents a real coming to terms with state violence.